PERLINDUNGAN HUKUM BAGI BANK TERHADAP PEMBLOKIRAN JAMINAN MILIK DEBITUR OLEH KEJAKSAAN - Farida, Mutiara; Rahardiansyah, Trubus (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract : This research aims to understand and examine the form of legal protection granted to banks as holders of collateral in the form of land and building rights owned by debtors, which have been encumbered with a security right (hak tanggungan) but were subsequently blocked by the Prosecutor's Office. This study employs a normative approach, primarily focusing on the analysis of applicable laws and regulations, supported by interviews with relevant sources. The methodological approaches used include the statute approach and the case approach. Based on the research findings, it was concluded that the Prosecutor's Office's action in blocking the land and building certificate used as collateral by the debtor does not eliminate the Bank’s rights as the holder of the security interest, as the Bank still receives legal protection.Keywords: Legal Protection, Bank, Security Rights, Blocking.